Paleozoic Laurentia-Gondwana interaction and the origin of the Appalachian-Andean mountain system - Dalziel, Ian W. D. (1994)
Laurentia, the rift-bounded Precambrian nucleus of North America, may have broken out from a Neoproterozoic supercontinent between East and West Gondwana. Several lines of evidence suggest that the Appalachian margin of Laurentia subsequently collided with the proto-Andean margin of the amalgamated Gondwana supercontinent in different relative positions during early and mid-Paleozoic time, in route to final docking against northwest Africa to complete the assembly of Pangea. Hence the Appalachian and Andean orogens may have originated as a single mountain system. The overall hypothesis retains the same paleomagnetic and paleobiogeographic controls as previous global reconstructions for the Paleozoic Era. Laurentia-Gondwana collisions may help to explain contemporaneous unconformities in the Paleozoic sedimentary cover of the Laurentian, Gondwanan, and Baltic cratons.